AB0538 Increased body mass index may not be a risk factor for the development of lupus nephritis. (12th June 2018) - Chock, Y.P.; Danve, A.; ,; Petri, M.; Fu, W.
Abstract : Background: Studies have indicated that elevated body mass index (BMI) increases risk of Chronic Kidney Disease (CKD). Obesity is a low grade inflammatory state which leads to CKD by glomerulosclerosis. Systemic Lupus Erythematosus (SLE) is associated with high leptin levels and dyslipidemia. We hypothesised that obese SLE patients may be at increased risk of nephritis. Objectives: We studied BMI as possible predictor for development of lupus nephritis (LN) in SLE. Methods: We performed a retrospective cross sectional study on a longitudinal lupus cohort. Patients were enrolled from year 1987 to 2015. We compared demographics, clinical information, labs between patients with and without LN (table 1) and between patients with SLE with and without obesity. Mean and standard deviations were reported for continuous variables. Number and percentages were shown for categorical variables and chi-square test was utilised for comparison. T- test was used to compare patients between the groups. Results: Total of 1362 patients with SLE fulfilling revised ACR criteria were included; 60.9% were Caucasian and 32.8% African American. 596 had biopsy-proven LN however 524 patients were excluded because they had proteinuria before or at cohort entry. Only first available BMI were analysed: 32.7% were obese (BMI >30 kg/m 2 ), 27.2% overweight (BMI: 25–29.9 kg/m 2 ), 37.5% normal (BMI: 18.5–24.9 kg/m 2 ) and 2.6% underweight (BMI <18.5 kg/m 2 ). 39.4% (537) patients were on steroids at first BMI measurement. Results are described in table 1. BMI measured as continuous (p=0.51) and categorical variables (overweight p=0.64, obese p=0.67) were not associated with LN after adjusting for age, sex and ethnicity. SLE patients with obesity were found to have lower disease activity (SLEDAI), proteinuria, dsDNA titers and higher complement levels. Conclusions: Obesity was not associated with the development of lupus nephritis. Obese patients with SLE had lower disease activity as measured by SLEDAI, dsDNA titers and complement levels. Disclosure of Interest: None declared